Case Report: A case of Tatton-Brown–Rahman syndrome featuring mitral annular disjunction and mitral valve prolapse due to a novel mutation site in the DNMT3A gene - Zhong-jiao Xu; Ru-ming Shen; Wu-ming Hu; Lin-chun Lv; Zhen-hua Shi; Li Lin (Frontiers in Cardiovascular Medicine)
A 13-year-old child presented with specific facial features, overgrowth, and intellectual disability. Echocardiography revealed the presence of a large pericardial effusion, left ventricular enlargement, mitral annular separation, and mitral valve prolapse with moderate regurgitation. These symptoms suggested a possible genetic disorder. High-throughput sequencing revealed a specific mutation in the DNMT3A gene (NM_175629.2:c.2408 + 1G > A) associated with Tatton-Brown–Rahman syndrome. The patient's condition was alleviated through accurate diagnosis and comprehensive treatment measures, including psychological and social support. Regular follow-ups to monitor the disease's progress and the effectiveness of treatment, along with timely adjustments to the treatment plan, can not only effectively reduce the child's symptoms and improve their quality of life but may also help prevent the potential risk of sudden death.